DEALING WITH JUVENILE DELINQUENCY: THE RELEVANCE OF ICELANDIC PREVENTION MODEL TO MALAYSIA - Ikhsan, Muhammad Izwan; Randawar, Daleleer Kaur; Kamarudin @ Abdul Shukor, Akbar (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
Juvenile delinquency is a growing concern in Malaysia. Previous studies indicate that reactive and punitive approach to address the issue has proven insufficient in addressing the root causes of child offending. This study explores the potential relevance of the Icelandic Prevention Model (IPM); an internationally acclaimed community-based approach to deal with juvenile delinquency. This study analyses the gaps in Malaysia’s current legislative approach to at-risk children and assesses the feasibility of adapting key components of the IPM into the Malaysian legal framework. This study employs a doctrinal research methodology by analysing statutory provisions and judicial interpretations as well as scholarly works written on the subject. It is supported by comparative analysis of the Icelandic and Malaysian laws on juvenile delinquency. Findings reveal that the success of IPM does not stem merely from imposing child’s curfews, but from incorporating them within a broader legal and social ecosystem, featuring youth activity regulations, parental accountability, school involvement, and municipal coordination. The study concludes that while cultural and systemic differences exist, adapting key aspects of the IPM could provide a viable pathway for Malaysia to improve its juvenile justice system and reduce delinquency rates.